2021
DOI: 10.1029/2020jg006144
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Riverine Freshwater Supply Changes Inorganic and Organic Carbon Dynamics and Air‐Water CO2 Fluxes in a Tropical Mangrove Dominated Estuary

Abstract: Estuaries are biogeochemically active zones where both particulate and dissolved matter undergoes vigorous transformations (Bianchi, 2007), mostly in ways that make these waters net heterotrophic (Gattuso et al., 1998;Testa et al., 2012), eventually leading to emission of substantial amounts of CO 2 to the atmosphere (Laruelle et al., 2010(Laruelle et al., , 2013. However, net autotrophy with the accompanying CO 2 sink is sometimes observed in some estuaries (Crosswell et al., 2017;Maher & Eyre, 2012). Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 117 publications
2
11
0
Order By: Relevance
“…DO exhibited no significant control on p CO 2 (water); thus, aerobic respiration of organic matter was not a major biogenic driver of p CO 2 (water). This result is consistent with the results of previous studies (Akhand et al 2021a,b) that physical mixing is dominant over biological controls as the major driver of p CO 2 (water) in the Hooghly and Matla estuaries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…DO exhibited no significant control on p CO 2 (water); thus, aerobic respiration of organic matter was not a major biogenic driver of p CO 2 (water). This result is consistent with the results of previous studies (Akhand et al 2021a,b) that physical mixing is dominant over biological controls as the major driver of p CO 2 (water) in the Hooghly and Matla estuaries.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies using hourly time series or discrete data have often underestimated or overestimated air–water gas fluxes because of their inability to capture tidal maxima and minima (Rosentreter et al 2018). Only one study, which collected data four times during an annual cycle, has reported high temporal resolution p CO 2 (water) and air–water CO 2 flux data for the Matla estuary (Akhand et al 2021b), and no previous study has to our knowledge collected high‐temporal‐resolution data from the Hooghly estuary. However, our air–water CO 2 flux data (Table 1) are also in good agreement with the annual data (hourly diurnal sampling twice each month) of Akhand et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no data exists to evaluate fresh groundwater contributions to estuarine pCO2 for Indian estuaries. However, Akhand et al (2021) reported porewater pCO2 values up to 5423 µatm in the Indian Sundarbans mangroves. Using mean annual soil temperature and porewater salinity from Dutta et al, (2013), we estimate that this equates to a CO2 concentration of 137 µM.…”
Section: Groundwater Co2 Sourcesmentioning
confidence: 95%
“…These estimates suggest a limited contribution of Indian estuaries to global estuarine CO2 and CH4 fluxes. In terms of anthropogenic greenhouse gas emissions, India emits 2.8 Gt CO2eq annually of which 79%, 14%, and 5% are contributed by CO2, CH4, Mangroves are both a large sink (i.e., soil C burial) and source of greenhouse gases to the atmosphere (Chauhan et al, 2008;Krithika et al, 2008;Dutta et al, 2013Dutta et al, , 2015Dutta et al, , 2017Barnes et al, 2011;Biswas et al, 2007;Akhand et al, 2021). Compiling a large mangrove dataset in the east coast of India, Banerjee et al (2014) estimated mean CO2 and CH4 fluxes from the mangrove surrounding water to be 20.18 mol m -2 yr -1 and 0.027 -17502 mmol m -2 yr -1 , respectively.…”
Section: Impact On Atmospheric C Budgetmentioning
confidence: 99%
See 1 more Smart Citation